Market dynamics and future prospects of the automobile industry in Saudi Arabia - Mohammad Rumzi Tausif; Mohammad Imdadul Haque (Problems and Perspectives in Management, 2018)
As the Kingdom of Saudi Arabia focuses on Vision 2030, there is an immediate need to establish some big manufacturing industries to create jobs and to generate revenue from non-oil sectors. Automobile is one such sector where demand is very high in the Kingdom. Local manufacturing can create a lot of jobs and revenue. This study tries to analyze the scope of automobile sector in the Kingdom. The objective here is to identify the functional value of cars, which can be useful for potential automobile manufacturers. A sample of population is asked about their satisfaction from cars based on five broad factors, namely safety, comfort, aesthetic, instrumentation and engine, through a recent primary survey conducted in 2018. Using structural equation modeling, the study finds that consumers in the Kingdom give maximum importance to the engine of the car. This finding would be helpful for designing the features of a local brand as per the preferences of the local market. Market dynamics indicates a strong consumer base. Future prospects are also promising, as there is strong domestic demand. This can be tapped if production is localized, leading to a development of an entire new manufacturing sector. Finally, the study discusses some feasible options for automobile manufacturing in the Kingdom.